تصورات المشروع المهني وعلاقته بقلق المستقبل لدى الطلبة المقبلين على التخرج - بوصبيع صالح, إيمان; حاج عمار, مفيدة (University of Eloued جامعة الوادي, 2023)
Summary The study aims to identify the perceptions of the professional project and its relationship to future anxiety among university students who will graduate in Eloued. The study focused on the following questions: Is there a relationship between the perceptions of the professional project and future anxiety among students who will graduate? Are there differences in the perceptions of the professional project among students who will graduate due to the gender variable? The vocational project among students who will graduate is attributed to the variable of specialization? Are there differences in the perceptions of the professional project among students who will graduate due to the academic level? Male and female students from three faculties of social sciences, humanities, science, technology, and economic sciences studying in the third year of a bachelor's degree and the second year of a master's degree at the University of Eloued. They were selected in a simple random way. To answer the questions of the study, the life project perception scale was applied to Zaqawa (2012) and the future anxiety scale of ZainebChakir (2012). 2015) and to find out the validity of the hypotheses or not, the correlation coefficient was used to find out the validity of the hypotheses, the correlation coefficient "Pearson" was used to detect the relationship between perceptions of the professional project and future anxiety, the test for the two independent samples to detect the differences between students in both variables for differences and the one-way analysis test. The following results were reached: There is a statistically significant correlation between the perceptions of the professional project and future anxiety among students who will graduate.
دراسة ميدانية لدى طلبة جامعة الشهيد حمه لخضربالوادي
مذكرة ماستر في علوم التربية تخصص ارشاد وتوجيه
Keywords: المشروع المهني، projet professionnel, professional project; قلق المستقبل، l'anxiété future, future anxiety